Experimental and numerical study on ultimate behaviour of high-strength steel tubular K-joints with external annular steel plates on chord circumference. (15th June 2018) - Qu, Song-Zhao; Wu, Xiao-Hong; Sun, Qing
Highlights: The external annular steel plates can improve the ultimate strength of joints. The ultimate strength of the joints increases with increasing D and t. The ultimate strength of the joints decreases with increasing axial compression ratio. The ultimate strength of joints is governed by local transverse plastic deformation. A formula has been developed whose results agree with the experimental results. Abstract: This study presents experimental and numerical studies on the ultimate behaviour of K-joints in transmission tubular structures. Tests were conducted on nine connection specimens using high-strength steel to investigate ultimate strength. The material properties and load–displacement responses of nine tubular K-joints are tested and discussed with emphasis on the factors that affect the ultimate strength of the joints. Based on the experimental and numerical results, the failure mode and mechanism of the high-strength steel K-joints are identified. Using energy theory and the virtual work principle, a formula for predicting the ultimate strength of high-strength steel K-joints is developed. In order to verify the validity of the proposed formula, finite element models are built to perform a sensitivity analysis on the parameters that affect the ultimate strength of the connections. The results indicate that the compression ratio of the chord and the thickness and diameter of the chord have significant effects on the ultimate strength of the K-joints with an external annular steel plate. Moreover, the results predicted by the proposed formula correlated very well with the experimental and numerical results.